Pazopanib-induced severe acute liver injury: A case report. Issue 46 (19th November 2021) - Choi, Jin-Wook; Yoo, Jeong-Ju; Kim, Sang Gyune; Kim, Young Seok; Chin, Susie
Abstract: Rationale: Drug-induced liver injury (DILI) is the most common cause of acute liver failure in the United States. Painkillers and fever antipyretics are the most common cause of DILI. Hepatic injury can be provoked by DILI as hepatocellular or cholestatic type. Patient concerns: A 48-year-old woman presented jaundice accompanied by nausea and vomiting. The patient was an inactive hepatitis B carrier with low viral titer and was diagnosed renal cell carcinoma (RCC) with hepatic metastasis requiring pazopanib treatment. Prior to administration of pazopanib, tenofovir administration was started to prevent exacerbation of hepatitis B. The patient was referred to clinic of gastroenterology department due to sudden elevation of bilirubin after 5 weeks of pazopanib treatment. Diagnoses: Abdominal ultrasound and computed tomography showed non-specific finding other than metastatic nodule in the liver and liver cirrhosis. After then, the patient was performed liver biopsy, and the biopsy result was acute cholestatic hepatitis with centrilobular area necrosis and portal inflammation. Therefore, considering the clinical history and biopsy results, the patient was diagnosed as DILI due to pazopanib. Interventions: After the biopsy, empirical steroid therapy was initiated and after 7 weeks of pazopanib discontinuation. Outcomes: The total bilirubin level returned to normal from peak level of 24.61 to 1.52 mg/dL. Lessons: In patients with renal cell carcinoma, pazopanib treatment requires clinical caution as it causes rare complications such as severe jaundice and acute cholestatic hepatitis.